Futsal Extracurricular Management Junior High School - Filli Azandi; Mawardinur, Mawardinur (Sekolah Tinggi Olahraga & Kesehatan Bina Guna, 2024)
The purpose of this study is basically to find answers to the problems that have been formulated above, namely how to manage futsal sports management at SMP Negeri 27 Medan so that it can continue to maintain the tradition of winning every tournament. Based on the results of the questionnaire calculations that have been carried out, it is known that the average questionnaire results measure futsal management starting from planning 84.09%, organizing 60.41%, implementing 78.03%, supervising 61.11%. From the results of the questionnaire test, it can be concluded that the extracurricular management of SMP Negeri 27 Medan researchers can conclude that the extracurricular management of futsal SMP Negeri 27 Medan has mostly been implemented with a percentage of 73.57% so extracurricular management is mostly implemented.